(untitled) (SCIENCE TIME JOURNAL, 2026)
This article investigates the problems of systematizing English suffixes and selecting their appropriate Uzbek correspondences within a contrastive linguistic framework. The study analyzes the functional and semantic characteristics of English suffixes and identifies major types of correspondence between English and Uzbek, including direct, partial, and zero correspondence. The findings demonstrate that due to typological differences between the two languages, suffix translation requires contextual and functional analysis rather than direct formal equivalence.